Validity and reliability of automated treadmill six-minute walk test in patients entering exercise-based cardiac rehabilitation - Nevelikova, Marketa; Dosbaba, Filip; Pepera, Garyfallia; Felsoci, Marian; Batalikova, Katerina; Su, Jing Jing; Batalik, Ladislav (Annals of medicine, 2023)
Introduction: The six-minute walk test (6MWT) is a well-established tool for assessing submaximal functional capacity for cardiac patients, but space limitations challenge its implementation. Treadmill-based (TR) 6MWT is a promising alternative, but it requires patients to complete a familiarization test to adapt treadmill speed regulation. With the advancement of sensors, it is possible to automatically control speed for individual patients and thus overcome the space limitation or the speed control difficulty on the treadmill for each patient.Methods: This study investigated the validity and interchangeability of automated speed TR6MWT and standard hallway (HL) 6MWT. Eighteen patients were assessed at baseline of the 12-week cardiac rehabilitation program. Fourteen of them were assessed after rehabilitation. All patients performed three TR6MWTs and three HL6MWTs at baseline and one of each test after the program.Results: Patients well tolerated the TR6MWT. There was a strong correlation between both test methods (r = 0.79). However, patients performed significantly better in HL6MWT (514.8m ± 59.7m) than in TR6MWT (447.2 ± 79.1m) with 95% CI, 40.4-94.6m, p < 0.05. Both tests showed high test-retest reliability (intraclass correlation coefficient of 0.86). The TR6MWT showed a valuable comparison of the effect of the cardiac rehabilitation program (20% increase, effect size 1.1) even though it is not interchangeable with the HL6MWT.Conclusion: The automated speed TR6MWT appears to be an acceptable tool with adequate validity, reliability, and responsiveness for assessing functional capacity in patients utilizing cardiac rehabilitation programs.
Keywords: reprodukovatelnost výsledků; kardiovaskulární rehabilitace; zátěžový test; Walking; chůze; test chůzí; Humans; Walk Test; lidé; Reproducibility of Results; Exercise Test; Cardiac Rehabilitation